Dropout Prevention Programs, 1985-1986. Progress Report - Quinones, Nathan; New York City Board of Education, Brooklyn, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This report provides an overview of the operation of two innovative New York City dropout prevention programs, the Attendance Improvement and Dropout Prevention Program (AIDP) and the Dropout Prevention Program (DPP). First, basic program components, required and site-specific, are described briefly. Each program site must provide these components: a site facilitator, an attendance outreach program, guidance and counseling services, a health services program, a school-level linkage program, and an alternative education program. Next, the status of program implementation through January 1986 is discussed. Statistics on 1985 attendance rates are compared to Fall 1984 rates. Characteristics of the targeted students are summarized, and month-by-month attendance for all participating schools is presented and analyzed in order to provide a preliminary picture of the programs' effects. General findings are that all components of both programs were fully implemented and operational by the end of 1985. Preliminary effects were an 0.8 percent increase in fall attendance at participating high schools, a decline of nearly 20 percent in the number of long-term absentees at participating high schools, an increased attendance at most AIDP middle schools, and an increase of 8.2 percent at special education AIDP sites. The report also includes detailed descriptions of several exemplary programs and an appendix presenting supplementary statistical information. (KH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attendance; Dropout Characteristics; Dropout Prevention; Dropout Programs; Dropout Rate; Nontraditional Education; Potential Dropouts; Program Effectiveness; Program Implementation; Secondary Education; Urban Schools; New York (New York); Reports, Evaluative; Numerical/Quantitative Data